PENGARUH BUDAYA ORGANISASI DAN KECERDASAN EMOSIONAL TERHADAP KINERJA KARYAWAN PADA HOTEL RESTY MENARA PEKANBARU - Uchi Satrya Awmarelita; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study was conducted at Resty Menara Pekanbaru Hotel where located on Sisingamangaraja,No. 102,Pekanbaru. The problem of this study is the target of the hotel room occupancy has not been achieved in the last four years, this is allegedly influenced by employee performance. This Study aims to determine the influence of organizational culture and emotional intelligence on employee performance in Resty menara Pekanbaru hotel.This study is using descriptive and quantitative analysis with the help of SPSS program. The target population comprised of 51 employees in Resty Menara Pekanbaru Hotel. The sampling chosen is based on census method that 51 persons that taken from overall target population. The method of data collection is done by distributing questionnaires. To test the hypothesis in this study is using simple linear analysis and analysis of multiple linear.The result of research indicates that for the t test, organizational culture and emotional intelligence partially have a significant effect on employee performance. And the result of F test indicates that organizational culture and emotional intelligence simultaneously have a significant effect on employee performance, with R square value of 0.319. This shows that the organizational culture and emotional intelligence have an influence of 31.9% on employee performance, while the remaining 68.1% is influenced by other variables not included in this study.Keywords: Organizational Culture, Emotional Intelligence, Employee Performance.